Profil Pranata Sosial Komunitas Suku Nuaulu (Studi Kehidupan Sosial Budaya Masyarakat Negeri Nua Nea di Maluku Tengah) - Anike J. M. Manuputty; Lodewyk Nahuway (Univiversitas Dr. Djar Wattiheluw, 2021)
Social institutions are rules that apply in regulating human behavior in acting based on considerations of norms and values inpeople's lives. This study aims to determine the existence and benefits of socio-cultural institutions in the Nuaulu tribal community. Data collection techniques with observation and in- depth interviews. Research informants from elements of the state government, traditional leaders, youth leaders, educators and community leaders. The results of the analysis conclude that customs from generation to generation have a very strong influence on the lives of the Nuaulu people with the loyalty of their people in carrying out existing institutions. Economic institutions and community livelihood systems are farming, processing sago, gathering, and labor. Socio- cultural institutional institutions in the form of adult ceremonies for boys (pataheri), adult ceremonies for girls (pinamou), marriage ceremonies, pregnancy ceremonies, birth ceremonies, hair ceremonies (tihtikuau) and death ceremonies. The kinship system is a male lineage and is not required to marry one another. Religious institutions and beliefs are tribal religions. Educational institutions, knowledge, and technology based on experience (local knowledge) from generation to generation, school age has been at various levels of education up to college.